Honey, the dog who saved Abe Lincoln - Swanson, Shari; Groenink, Chuck (New York : Katherine Tegen Books, 2020)
Based on primary sources, the true story of Abraham Lincoln being rescued from a cave by his rescue dog.
School Library Journal, December 2019
Booklist, November 2019
Kirkus Review, October 2019
2.5
K-3
670L
Keywords: Lincoln, Abraham, -- 1809-1865 -- Childhood and youth -- Juvenile literature; Dogs -- Juvenile literature; Rescues -- Juvenile literature; Lincoln, Abraham, 1809-1865 -- Childhood and youth; Dogs; Rescue work; Creative nonfiction